Interlanguage Pragmatics: A Study of Iraqi EFL Learners’ Realization of Complaint Speech Acts - Al-Shareef, Sumaya (Indonesian Journal of Humanities and Social Sciences, 2023)
This study investigates the interlanguage pragmatic competence of Iraqi EFL learners in the performance of the speech act of complaining. The study explores the semantic components of the complaint speech act produced by Iraqi EFL learners in their interlanguage and compares their performance with that of English native speakers. Additionally, it examines the extent to which social variables such as power and distance influence the performance of the speech act of complaining by both Iraqi EFL learners and English native speakers. The study used a mixed-methods approach, combining quantitative and qualitative data. The quantitative data consisted of the results of a discourse completion test (DCT) that was administered to 100 Iraqi EFL learners and 11 English native speakers. The qualitative data consisted of transcripts of interviews with 20 of the DCT participants. The findings of the study showed that Iraqi EFL learners use a variety of strategies to realize complaint speech acts in English. The most frequently used strategies were criticism, demand, and complaint. Justification and request were also used with high frequency. Apology and warning were produced with a relatively low frequency. Explanation of purpose was the least used semantic component in complaining in the EFL group. There were significant differences in the mean scores of the semantic components between Iraqi EFL learners and English native speakers. Iraqi EFL learners need to be more aware of the different semantic components of complaint speech acts in English and how to use them appropriately in different contexts. Additionally, teachers should be sensitive to the cultural differences between English and Arabic when teaching Iraqi EFL learners about complaint speech acts.